: Bernie the biography of Bernie Ecclestone - Susan Watkins (Sparkford : Haynes, 2011)
Bernie Ecclestone is best-known as the architect and figurehead of modern F1, but he has been a constant and often controversial presence in both F1 and British public life since the 1970s. This